Penguatan Literasi Manajemen Sumber Daya Manusia melalui Pengajian Mingguan di Masjid Kramatwatu - Suhartini Suhartini (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2026)
This community service activity aimed to enhance human resource management (HRM) literacy among congregation members through weekly religious study sessions at Kramatwatu Mosque. HRM literacy is important not only in formal work environments, but also in family life, social organizations, and religious activities. The problem identified was the congregation’s limited understanding of basic HRM concepts, such as planning, organizing, role distribution, discipline, communication, and individual potential development. The community service program was carried out through an educational-participatory approach in the form of material presentation, interactive discussions, simple case studies, and reflection on Islamic values relevant to human resource management. The activity was implemented gradually in weekly religious study forums by taking into account the characteristics of the congregation. The results showed an improvement in the congregation’s understanding of the importance of HRM in daily life, particularly in the aspects of responsibility, cooperation, discipline, and self-capacity development. Weekly religious study sessions proved effective as a medium for community empowerment because they were able to integrate religious values with practical HRM concepts. Therefore, strengthening HRM literacy through weekly religious study sessions can serve as a relevant educational strategy to improve mosque-based human resource quality.